Efficacy and Safety of Tirofiban in Clinical Patients With Acute Ischemic Stroke - Han, Bin; Ma, Teng; Liu, Zhendong; Wu, Yiqun; Tan, Weiwei; Sun, Shaoyang; Li, Xuemei; Shao, Changyan; Tang, Duyong; Sun, Jinping (Frontiers in Neurology, 2022)
Background Intravenous thrombolysis and endovascular thrombectomy have been approved for acute ischemic stroke (AIS). However, only a minority of patients received these treatments in China. We aimed to evaluate the efficacy and safety of tirofiban in patients with AIS who were not undergoing early recanalization treatments. Methods Patients with mild-to-moderate stroke [National Institutes of Health Stroke Scale (NIHSS) score, 4–15] were enrolled in this study. Patients due to cardiogenic embolism were excluded. Eligible patients within 12 h from symptom onset were randomly assigned (1:1) to receive tirofiban (a loading dose of 0.4 μg/kg/min over 30 min and a maintenance dose of 0.1 μg/kg/min up to 48 h) followed by regular treatment or to receive regular treatment (aspirin at a dose of 100 mg per day for 90 days) (control). The primary outcome was the proportion of favorable functional outcomes at 90 days [defined as the modified Rankin Scale (mRS) score of 0–2]. The secondary outcomes included a shift in the distribution of the mRS scores at 90 days and the NIHSS score at 24 h and 7 days. The primary safety outcome was symptomatic intracranial hemorrhage (sICH) within 7 days after tirofiban treatment. Results A total of 380 eligible patients were randomly assigned to the tirofiban group (n = 190) or the control group (n = 190). The proportion of favorable functional outcomes was higher in the tirofiban group (79.1%) than that in the control group (67.8%) at 90 days [odds ratio (OR), 1.80; 95% CI, 1.12–2.90; p = 0.0155]. An improvement was also observed in the overall distribution of the 90-day mRS scores (adjusted common OR, 2.31; 95% CI, 1.58–3.39; p < 0.0001). Additionally, the median NIHSS score was lower in the tirofiban group than in the control group at 7 days (3 vs. 5, p < 0.0001). Next, we observed that the occurrence of sICH did not differ between the two groups. Conclusion Our trial supports that tirofiban was safe and effective and might be a remedial treatment for patients with AIS who did not receive recanalization treatments. Clinical Trial Registration http://www.chictr.org.cn/, identifier: ChiCTR2000031297.